The Development of Personality Ontology Based on the Methontology Approach - Zakaria, Zalmiyah; Kasim, Shahreen; Husna Mohamad Hasbullah, Nur; Alyani Azadin, Ayu; Saleh Ahmar, Ansari; Hidayat, Rahmat (International Journal of Engineering and Technology, 2018)
Complex domain occurs when a lot of knowledge overloads and knowledge trek phenomenon appeared with the raise of product complexity and the explosion of knowledge and information.Â The knowledge content of complex domain is difficult to organize. One of the complex domain is Fingerprint Fingerprint Personality Solution. However, it is difficult to organize the knowledge of Fingerprint solution since it is a complex domain. Knowledge acquisition also a part of the problem because there is an only little number of Fingerprint certified trainer that expert in Fingerprint solution. The other circumstances are an Fingerprint solution also have the possibility to be extended in future. To solve the following problem, Structured Knowledge is used to structure the knowledge content that will be more effectively organize the content in order to enhance reusable and extendable of the knowledge model. Structured Knowledge contains a wealth information, it can effectively help to carry out the knowledge of the complex domain. There are many ways to express the structured knowledge, Ontology is one of them. In this paper will discuss the development of Fingerprint Ontology based on METHONTOLOGY approach.Â Â